A PKA-selective inhibitor captures an open but more ordered conformation of the PKA catalytic subunit - Jessica G. H. Bruystens; Jian Wu; Gerald Tan; Daniela Bertinetti; Hans-Michael Zenn; Bastian Zimmermann; Lisa Chen; Johannes Köckenberger; Federica Massaro; Banumathi Sankaran; Matthew S. Walters; Gianluigi Veglia; et al. (Proceedings of the National Academy of Sciences, 2026)
The structure of the catalytic subunit of cAMP-dependent protein kinase (PKA-C), a prototype for the protein kinase superfamily, laid the foundation for the development of targeted kinase inhibitors. Here we describe the structure and biophysical characterization of a PKA-C complex with BLU0588, a small PKA-selective inhibitor. The high-resolution crystal structure not only captures the inhibitor’s unusual T-shaped geometry, but also shows how the four rings of BLU0588 serve as surrogates for ATP’s adenosine and phosphate-organizing sites. Each site contains two subsites. BLU0588’s planar azaindole and pyridine rings, which are buried beneath the glycine-rich loop in a hydrophobic shell at the base of the active site cleft, fill the adenine and ribose subsites. In contrast, BLU0588’s indane and pyrrolidine rings fill the phosphate-organizing site. The indane ring occupies the α/β-phosphate organizing site while the pyrrolidine ring fills the Mg/γ-phosphate organizing site. The structure also shows how BLU0588 nucleates an open but stable conformation of the entire hydrophobic architecture of the N- and C-lobes. In addition to potently blocking phosphoryl transfer activity, BLU0588 also abolishes the synergistic high-affinity binding of the physiological pseudosubstrate inhibitor, protein kinase inhibitor. The residence time of BLU0588, measured by surface plasmon residence, contributes to its picomolar affinity and is distinct from H89, a commonly used but more promiscuous PKA inhibitor. These molecular insights provide a valuable framework for dissecting the organization of the active site cleft as well as different strategies for the rational design of more potent and selective kinase inhibitors in general.